The Different Jurisprudence Methods Cause the Islamic Law View Differences (Zakat Example) - KAAN, ENVER OSMAN (DINBILIMLERI AKAD ARASTIRMA MERKEZI, 2020)
The rules of fiqh, the foundations of which were laid in the first age and geography of Islam, were later developed by Islamic scholars and turned into methods. Because the production of fiqh rulings within the framework of a method is thought to play an important role in the establishment of a fiqh stable structure. Over time, these methods have proliferated with the force of regional conditions. As it is known, three different methods have emerged in the science of procedure, mutakallim, fuqaha and mamzuj. Therefore, it is not possible to talk about a single method in establishing fiqh judgments. The difference in method naturally brings along the difference of fiqh views. Within the framework of a certain method, the reasons for the differences in views are explained in the fiqh books in a scattered way. Although recent studies in the field of comparative Islamic law show a scattered approach to juridical disagreements, they still give a scattered image. In this article, it is aimed to explain together the causes of juridical differences of opinion, which are also closely related to comparative law. In addition, as a specific example with the idea that it serves the purpose, the subject will be enriched through zakat.
Keywords: Fiqh; Zakah (Almsgiving); Jurisprudence (Ijtihad); Method; Ruling